Exploratory and factor validation and psychometric properties of quality of customer service delivery by local authority / Zikri Muhammad ...[et al.] - Muhammad, Zikri; Rostam, Katiman; Mohd. Yusoff, Yusliza; Manaf Bohari, Abdul (Universiti Teknologi MARA, Perlis, 2010)
This study adds to the quality of service delivery by local government literature, particularly within a Malaysian context. The quality of service delivery is measured based on service delivery information provided from Kajang Municipal Council Annual Report 2006. The sample of the present study consisted of 638 residents in Kajang residential area and had utilized a stratified random sampling method to collect data. The study proposes that quality of service delivery having seven dimensions by using exploratory factor analysis with varimax rotation: complaining services, community development services, law enforcement services, environmental management services, basic amenities services, community health services, and street and light services. Means and Standard Deviations, ANOVA and independent sample t-test were used to determine any differences among the mean scores for each dimensions of quality of service delivery with gender, project type, race, ownership status, educational background, marital status, household income, and age. Major findings of this study shows that project type is differ significantly for basic amenities services, street and light services, environmental management services, community health services and complaining services. Meanwhile household income group shows significantly with basic amenities, street and light services and environmental management services